Preparation method and application of iron-based selenide / carbon nanotube composite material

By using iron-based selenide/carbon nanotube composite materials as the negative electrode material for sodium ion batteries, the problem of poor operating performance of existing sodium ion batteries at high magnifications has been solved, and the electrochemical performance has been significantly improved.

CN115775873BActive Publication Date: 2025-04-11GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211593417.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-09
Publication Date
2025-04-11
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

Existing sodium ion batteries have problems with low output current density, poor reversible capacity and rate performance, resulting in poor operating performance at high rates.

Method used

Iron-based selenide/carbon nanotube composite material is used as the negative electrode material for sodium ion batteries. By mixing stainless steel powder with carbon nanotubes and heat-treated with selenium powder, composite material with excellent conductivity is prepared.

Benefits of technology

It significantly improves the electrochemical performance of sodium ion batteries, including rate performance and charge and discharge performance, making the battery run more stable and efficient at high magnifications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115775873B_ABST
    Figure CN115775873B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of an iron-based selenide / carbon nanotube composite material, belonging to the technical field of sodium ion battery electrode materials. The present invention adopts a two-step method to prepare an iron-based selenide / carbon nanotube composite material, wherein the iron-based selenide can play a role in improving electrical conductivity, and at the same time, carbon nanotubes can further improve the electrochemical performance of sodium ion batteries due to their excellent electrical conductivity; the present invention obtains a composite material with high rate performance by controlling the mass ratio of stainless steel powder and carbon nanotubes, heat treatment temperature and other parameters during the preparation process, which can maximize the electrochemical performance of sodium ion batteries; the preparation process of the present invention does not require the addition of chemical reagents, the preparation process is simple, and multi-phase selenides can be prepared, which reasonably utilizes the advantages of each component itself, enhances the electrochemical performance of sodium ion batteries, and promotes the realization of sodium ion battery industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery electrode materials, and in particular to a preparation method and application of an iron-based selenide / carbon nanotube composite material. Background Art

[0002] With the soaring international energy prices and my country's high dependence on foreign oil, from the perspective of energy security and reducing foreign exchange consumption, my country is in urgent need of alternative energy options, and vigorously developing renewable energy has become the optimal solution to the above problems. However, renewable energy generally has the problem of scattered distribution in time and space, which requires the combination of energy storage devices to make renewable energy practical. As the most widely used energy storage device, the research on power batteries has received widespread attention.

[0003] At present, the power battery market has always been centered on lithium-ion batteries. Lithium-ion batteries have the advantages of high discharge voltage, low self-discharge, long cycle life, no pollution and no memory effect, but metallic lithium is expensive, and it is difficult for lithium-ion batteries to effectively increase the output current density, which is contrary to the original intention of power batteries. Relatively speaking, metallic sodium has a wide source, simple purification process, and low price, and has gradually become the object of research in the power battery market; however, because the radius of sodium ions is larger than that of lithium, they migrate slowly in electrode materials, and the deintercalation process is complicated, resulting in reduced reversible capacity and rate performance. Therefore, there are still many problems in the research of negative electrode materials for sodium-ion batteries.

[0004] In view of the above-mentioned defects of sodium-ion batteries, finding a sodium-ion battery electrode material that is inexpensive and can operate at high rates is the current research focus in the field of sodium-ion batteries. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a method for preparing an iron-based selenide / carbon nanotube composite material and its application. The iron-based selenide / carbon nanotube composite material prepared by the method can be used as a negative electrode material of a sodium ion battery to effectively improve the electrochemical performance of the sodium ion battery.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a method for preparing an iron-based selenide / carbon nanotube composite material, the method comprising the following steps:

[0008] S1, mixing stainless steel powder and carbon nanotubes and ball milling to obtain mixed powder, wherein the mass ratio of the stainless steel powder to the carbon nanotubes is 140:(0-14);

[0009] S2. Place the mixed powder and selenium powder described in step S1 in the same device for heat treatment, wherein the mass ratio of the mixed powder to the selenium powder is 1:3, the heat treatment temperature is 450-650°C, the heat treatment time is 1-7h, and the heating rate is 1-5°C / min. After the heat treatment, the iron-based selenide / carbon nanotube composite material is obtained.

[0010] The present invention adopts carbon nanotubes with excellent electrical conductivity and stainless steel powders of various types, cheap and easily available as reaction raw materials, and mixes them by ball milling to obtain mixed powders. The stainless steel powders and carbon nanotubes interact with each other under mechanical collision, which is safe and convenient. While ensuring the ideal mixing effect, the reaction process is shortened, the economic and time costs of production are reduced, and the problems of the need to add various chemical reagents and complex synthesis atmosphere in the current synthesis process of such mixed powders are overcome. The present invention heat-treats the mixed powder together with selenium powder, and the selenium powder at one end of the porcelain boat generates selenium vapor when heated. The selenium vapor selenizes the metal in the stainless steel powder to generate iron-based selenide, which can improve the conductivity of the composite material, and the carbon nanotubes in the composite material also have excellent conductivity, which can improve the conductivity of the negative electrode material to further improve the electrochemical performance of the sodium ion battery.

[0011] The inventors further discovered that when the stainless steel powder and the carbon nanotubes are in the above mass ratio, the prepared iron-based selenide / carbon nanotube composite material can significantly improve the electrochemical performance of the final sodium ion battery.

[0012] The inventors also found that the temperature of the heat treatment has a significant effect on the product type of the iron-based selenide. When the heat treatment temperature is within the range provided by the present invention, the electrochemical performance of the final sodium ion battery can be optimized.

[0013] The inventors also found that when the mass ratio of the mixed powder to the selenium powder is the above ratio, the metal in the mixed powder can be fully selenized, thereby improving the electrochemical performance of the final sodium ion battery without causing waste of selenium powder.

[0014] As a preferred embodiment of the method for preparing the iron-based selenide / carbon nanotube composite material of the present invention, in the step S1, the mass ratio of the stainless steel powder to the carbon nanotubes is 140:(1-14). The inventors have found through a large number of experiments that the iron-based selenide / carbon nanotube composite material prepared at this mass ratio of the stainless steel powder to the carbon nanotubes can greatly improve the electrochemical performance of the sodium ion battery, making the battery's rate and charge and discharge performance excellent.

[0015] As a more preferred embodiment of the method for preparing the iron-based selenide / carbon nanotube composite material of the present invention, in the step S1, the mass ratio of the stainless steel powder to the carbon nanotubes is 20:1. The inventors have found through a large number of experiments that the iron-based selenide / carbon nanotube composite material prepared at this mass ratio of stainless steel powder to carbon nanotubes can maximize the electrochemical performance of the sodium ion battery, making the battery's rate and charge and discharge performance excellent.

[0016] As a preferred embodiment of the method for preparing the iron-based selenide / carbon nanotube composite material of the present invention, in step S1, the carbon nanotubes are amino-treated multi-walled carbon nanotubes.

[0017] As a preferred embodiment of the method for preparing the iron-based selenide / carbon nanotube composite material of the present invention, in step S1, the stainless steel powder is 420 type stainless steel powder.

[0018] As a preferred embodiment of the method for preparing the iron-based selenide / carbon nanotube composite material of the present invention, in the step S1, the ball milling parameters are: a rotation speed of 500-1800 rpm, and a ball milling time of 30-100 min.

[0019] It should be noted that, since the ball milling time of the present invention is relatively long, in order to avoid overheating and damage of the ball mill due to long-term operation, an intermittent ball milling method is adopted for ball milling mixing, which is characterized by pausing for 5-10 minutes every 15-30 minutes of ball milling and repeating until the required ball milling time.

[0020] As a preferred embodiment of the method for preparing the iron-based selenide / carbon nanotube composite material of the present invention, in the step S1, the ball milling jar used for ball milling is made of stainless steel, polytetrafluoroethylene, zirconium oxide or agate.

[0021] As a preferred embodiment of the method for preparing the iron-based selenide / carbon nanotube composite material of the present invention, in step S2, the heat treatment process is specifically as follows: placing the mixed powder and selenium powder at both ends of a porcelain boat respectively and putting them into a tubular furnace for heat treatment under an inert atmosphere.

[0022] As a more preferred embodiment of the method for preparing the iron-based selenide / carbon nanotube composite material of the present invention, in the step S2, the heat treatment temperature is 550°C. The inventors have found through a large number of experiments that when the heat treatment temperature is 550°C, the electrochemical performance of the sodium ion battery is optimal, and the battery's rate and charge and discharge performance are excellent.

[0023] As a more preferred embodiment of the method for preparing the iron-based selenide / carbon nanotube composite material of the present invention, in step S2, the porcelain boat is tightly wrapped with carbon paper and then placed in a tubular furnace, in order to prevent the gas from blowing away the powder and foreign impurities from contaminating the sample, thereby affecting the selenization efficiency and product purity.

[0024] As a more preferred embodiment of the preparation method of the iron-based selenide / carbon nanotube composite material of the present invention, the selenium powder is placed on one side of the air inlet, and the mixed powder is placed on one side of the air outlet. Placing the selenium powder at the air inlet allows the selenium vapor to fully fill the porcelain boat along the direction of the air flow, so that the metal in the mixed powder can be selenized more completely.

[0025] As a more preferred embodiment of the method for preparing the iron-based selenide / carbon nanotube composite material of the present invention, in step S2, the heat treatment is performed under an inert atmosphere.

[0026] As the most preferred embodiment of the method for preparing the iron-based selenide / carbon nanotube composite material of the present invention, the inert atmosphere is argon or nitrogen.

[0027] In a second aspect, the present invention provides an iron-based selenide / carbon nanotube composite material, which is prepared by the preparation method of the iron-based selenide / carbon nanotube composite material as described in the first aspect.

[0028] In a third aspect, the present invention provides a negative electrode sheet for a sodium ion battery, wherein the raw materials for preparing the negative electrode sheet for a sodium ion battery include the iron-based selenide / carbon nanotube composite material as described in the second aspect.

[0029] As a preferred embodiment of the negative electrode sheet of a sodium ion battery of the present invention, the raw materials for preparing the negative electrode sheet of the sodium ion battery further include conductive carbon black and polyvinylidene fluoride.

[0030] As a more preferred embodiment of the negative electrode sheet of the sodium ion battery of the present invention, the mass ratio of the iron-based selenide / carbon nanotube composite material to the conductive carbon black and polyvinylidene fluoride is: iron-based selenide / carbon nanotube composite material: conductive carbon black: polyvinylidene fluoride = (7-8): (1-2): 1.

[0031] The present invention also provides a method for preparing the negative electrode sheet of the sodium ion battery, comprising the following steps: grinding and mixing an iron-based selenide / carbon nanotube composite material, conductive carbon black and polyvinylidene fluoride, dropping N-methyl pyrrolidone, stirring evenly, and evenly applying the obtained slurry on the rough surface of the current collector and vacuum drying to obtain the negative electrode sheet of the sodium ion battery, wherein the mass ratio of the N-methyl pyrrolidone to the mixed material of the iron-based selenide / carbon nanotube composite material, conductive carbon black and polyvinylidene fluoride is (154.2-514.0):50.

[0032] As a preferred embodiment of the method for preparing the negative electrode sheet of a sodium ion battery of the present invention, the current collector is copper foil.

[0033] In a fourth aspect, the present invention provides a button battery, wherein the button battery is prepared using the sodium ion battery negative electrode sheet as described in the third aspect.

[0034] As a preferred embodiment of the button cell of the present invention, the negative electrode material of the button cell is metallic sodium, and the electrolyte of the electrolyte is sodium hexafluorophosphate.

[0035] In a fifth aspect, the present invention also provides an application of an iron-based selenide / carbon nanotube composite material in the preparation of a negative electrode sheet for a sodium ion battery.

[0036] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adopts a two-step method to prepare an iron-based selenide / carbon nanotube composite material, wherein the iron-based selenide can act as the main sodium storage material, and at the same time, the carbon nanotubes can further improve the conductivity of the composite material due to their excellent electrical conductivity, thereby improving the overall electrochemical performance; the present invention obtains a composite material with high rate performance by controlling parameters such as the mass ratio of stainless steel powder and carbon nanotubes and the heat treatment temperature during the preparation process, which can maximize the electrochemical performance of sodium ion batteries; the preparation process of the present invention does not require the addition of chemical reagents, the preparation process is simple, and multi-phase selenides can be prepared, and the advantages of each component itself are reasonably utilized to obtain better sodium ion battery performance, thereby promoting the industrialization of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is an X-ray diffraction spectrum of the iron-based selenide / carbon nanotube composite material according to an embodiment of the present invention;

[0038] Figure 2 for Figure 1 A scanning electron microscope image of the iron-based selenide / carbon nanotube composite material;

[0039] Figure 3 is an X-ray diffraction spectrum of the iron-based selenide / carbon nanotube composite material according to another embodiment of the present invention;

[0040] Figure 4 for Figure 3 A scanning electron microscope image of the iron-based selenide / carbon nanotube composite material;

[0041] Figure 5 is an X-ray diffraction spectrum of the iron-based selenide / carbon nanotube composite material according to another embodiment of the present invention;

[0042] Figure 6 for Figure 5 A scanning electron microscope image of the iron-based selenide / carbon nanotube composite material;

[0043] Figure 7 is an X-ray diffraction spectrum of the iron-based selenide / carbon nanotube composite material according to another embodiment of the present invention;

[0044] Figure 8for Figure 7 A scanning electron microscope image of the iron-based selenide / carbon nanotube composite material;

[0045] Fig. 9 is an X-ray diffraction spectrum of the iron-based selenide / carbon nanotube composite material according to another embodiment of the present invention;

[0046] Fig.10 for Fig. 9 A scanning electron microscope image of the iron-based selenide / carbon nanotube composite material;

[0047] Fig.11 for Figure 1 , Figure 3 , Figure 5 The iron-based selenide / carbon nanotube composite material has a -1 The results of long cycle stability test at current density of ;

[0048] Fig.12 for Figure 1 , Figure 3 , Figure 5 Performance comparison of the iron-based selenide / carbon nanotube composite material in charge and discharge tests at different current densities;

[0049] Fig.13 for Figure 1 Cyclic voltammetry curve of the iron-based selenide / carbon nanotube composite material;

[0050] Fig.14 for Figure 1 , Figure 7 , Fig. 9 The iron-based selenide / carbon nanotube composite material has a -1 The results of long cycle stability test at current density of ;

[0051] Fig.15 for Figure 1 , Figure 7 , Fig. 9 Performance comparison of the iron-based selenide / carbon nanotube composite material in charge and discharge tests at different current densities. DETAILED DESCRIPTION

[0052] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0053] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0054] Example 1

[0055] The preparation method of the iron-based selenide / carbon nanotube composite material described in this embodiment comprises the following steps:

[0056] S1. 140 mg of 420 stainless steel powder and 7 mg of amino-modified multi-walled carbon nanotubes were sealed in a stainless steel ball mill, and ball milled continuously for 1 h at a speed of 1800 rpm for 4 times (15 min of ball milling and 5 min of pause after each ball milling, and the ball milling time does not include the pause time) to obtain a mixed powder;

[0057] S2. Place the mixed powder described in step S1 and 441 mg of selenium powder at both ends of a porcelain boat respectively, wrap them with carbon paper and place them in a tube furnace. Heat the mixture to 550°C at a heating rate of 1°C / min in a nitrogen atmosphere and keep the temperature for 3 hours to obtain an iron-based selenide / carbon nanotube composite material.

[0058] The X-ray diffraction spectrum of the iron-based selenide / carbon nanotube composite material described in this embodiment is as follows: Figure 1 As shown, the peak positions and peak intensities of its X-ray diffraction spectrum correspond to the standard cards of Fe3Se4 and Cr2Se3, proving that the main components of the iron-based selenide / carbon nanotube composite material of this embodiment are Fe3Se4 and Cr2Se3.

[0059] The scanning electron microscope image of the iron-based selenide / carbon nanotube composite material described in this example is as follows Figure 2 As shown, its microstructure presents block distribution of different sizes and shapes, and a small amount of carbon nanotubes can be seen occasionally in the figure.

[0060] Example 2

[0061] The difference between this embodiment and embodiment 1 is that in step S1, carbon nanotubes are not added, and the remaining steps are consistent with embodiment 1.

[0062] The X-ray diffraction spectrum of the iron-based selenide / carbon nanotube composite material described in this embodiment is as follows: Figure 3 As shown, the peak positions and peak intensities of its X-ray diffraction spectrum correspond to the standard cards of Fe3Se4 and Cr2Se3, proving that the main components of the iron-based selenide / carbon nanotube composite material of this embodiment are Fe3Se4 and Cr2Se3.

[0063] The scanning electron microscope image of the iron-based selenide / carbon nanotube composite material described in this embodiment is as follows Figure 4 As shown, its microstructure presents block distribution of different sizes and shapes.

[0064] Example 3

[0065] The difference between this embodiment and embodiment 1 is that in step S1, the mass of the aminated multi-walled carbon nanotubes is 14 mg, and the other steps are consistent with embodiment 1.

[0066] The X-ray diffraction spectrum of the iron-based selenide / carbon nanotube composite material described in this embodiment is as follows: Figure 5 As shown, the peak position and peak intensity of its X-ray diffraction spectrum are in correspondence with the standard card of Fe3Se4, proving that the main component of the iron-based selenide / carbon nanotube composite material in this embodiment is Fe3Se4.

[0067] It should be noted that a small amount of Cr2Se3 also exists in the final product of this embodiment, but its peak position in the X-ray diffraction spectrum is weak and is covered by the peak position of Fe3Se4.

[0068] The scanning electron microscope image of the iron-based selenide / carbon nanotube composite material described in this embodiment is as follows Figure 6 As shown, its microstructure presents block distribution of different sizes and shapes.

[0069] Example 4

[0070] The only difference between this embodiment and embodiment 1 is that in step S2, the heat treatment temperature is 450°C and the holding time is 3 hours, and the remaining steps are consistent with embodiment 1.

[0071] The X-ray diffraction spectrum of the iron-based selenide / carbon nanotube composite material described in this embodiment is as follows: Figure 7 As shown, the peak positions and peak intensities of its X-ray diffraction spectrum correspond to the standard cards of FeSe2 and Fe3Se4, proving that the main components of the iron-based selenide / carbon nanotube composite material of this embodiment are FeSe2 and Fe3Se4.

[0072] The scanning electron microscope image of the iron-based selenide / carbon nanotube composite material described in this embodiment is as follows Figure 8 As shown, its microstructure presents block distribution of different sizes and shapes.

[0073] Example 5

[0074] The difference between this embodiment and embodiment 1 is that in step S2, the temperature of the heat treatment is 650°C, and the other steps are consistent with embodiment 1.

[0075] The X-ray diffraction spectrum of the iron-based selenide / carbon nanotube composite material described in this embodiment is as follows: Fig. 9 As shown, the peak positions and peak intensities of its X-ray diffraction spectrum correspond to the standard cards of Fe7Se8 and Cr2Se3, proving that the main components of the iron-based selenide / carbon nanotube composite material of this embodiment are Fe7Se8 and Cr2Se3.

[0076] The scanning electron microscope image of the iron-based selenide / carbon nanotube composite material described in this embodiment is as follows Fig.10 As shown, its microstructure presents block distribution of different sizes and shapes.

[0077] Experimental example

[0078] The iron-based selenide / carbon nanotube composite material described in Examples 1-5 is used as the main negative electrode material to assemble a sodium ion battery. The preparation method of the negative electrode sheet of the sodium ion battery is: the iron-based selenide / carbon nanotube composite material, conductive carbon black and polyvinylidene fluoride are ground and mixed in a mass ratio of 7:2:1, an appropriate amount of N-methylpyrrolidone is added dropwise and stirred evenly, the obtained slurry is applied to the rough surface of the copper foil and vacuum dried to obtain the negative electrode sheet of the sodium ion battery, the electrode sheet is placed in a glove box and a button battery is assembled, wherein the negative electrode material is metallic sodium, and the electrolyte is a 1.0M diethylene glycol dimethyl ether solution of NaPF6. The performance test results of the sodium ion batteries described in Examples 1-5 are as follows Figure 11-15 shown.

[0079] Figure 11-15 The results show that the first cycle charging capacity of the battery in Example 1 is 426.86 mAh g -1 , the discharge capacity is 489.14 mAh g -1 The first cycle charge and discharge efficiency is 87.27%; the first cycle charge specific capacity of the battery in Example 2 is 167.88 mAh g -1 , the discharge capacity is 216.66 mAh g -1 The first cycle charge and discharge efficiency is 77.48%; the first cycle charge specific capacity of the battery in Example 3 is 358.49 mAh g -1 , the discharge capacity is 454.25mAh g -1 The first cycle charge and discharge efficiency is 78.92%; the first cycle charge specific capacity of the battery in Example 4 is 380.44 mAh g -1 , the discharge capacity is 472.86 mAh g -1 The first cycle charge and discharge efficiency is 80.46%; the first cycle charge specific capacity of the battery in Example 5 is 363.42 mAh g -1 , the discharge capacity is 436.84 mAh g -1 The first cycle charge and discharge efficiency is 83.19%. -1 After 200 cycles at a current density of 0.5A g, the capacity retention rates of Examples 1, 3, and 5 are all close to 100%, 70.74% for Example 2, and 94.69% for Example 4. -1 , 1A g -1 , 2A g -1 , 5A g -1 , 10A g -1 , 15A g -1 , 20A g -1 , 25A g -1 、30A g-1 , 50Ag -1 The first cycle discharge capacity of the battery in Example 1 is 506.50 mAh g -1 , 429.16mAh g -1 、410.61mAh g -1 、388.92mAhg -1 , 366.94mAh g -1 、350.09mAh g -1 , 333.40mAh g -1 , 319.48mAh g -1 , 308.37mAh g -1 , 263.92mAh g -1 , the rate finally returned to 0.5A g -1 , the discharge capacity is 424.43 mAh g -1 In Example 2, the rate finally returned to 0.5A g -1 , the discharge capacity is 319.55 mAh g -1 In Example 3, the rate finally returned to 0.5A g -1 , the discharge capacity is 351.12 mAh g -1 In Example 4, the rate finally returned to 0.5A g -1 , the discharge capacity is 364.17 mAh g -1 In Example 5, the rate finally returned to 0.5A g -1 , the discharge capacity is 350.52 mAh g -1 It can be seen that the rate performance of Example 1 is the best, and in the first cycle of the battery of Example 1, there is an oxidation peak at 1.51V and 2.26V, and the reduction peaks appear at 1.15V, 0.83V, 0.63V and 0.55V. The oxidation peaks of the second cycle appear at 1.51V, 1.98V and 2.27V, and the reduction peaks are at 1.92V, 1.73V, 1.32V, 0.79V and 0.60V. The positions of the redox peaks of the third cycle are almost the same as those of the second cycle.

[0080] In summary, the iron-based selenide / carbon nanotube composite material prepared at a mass ratio of 20:1 between stainless steel powder and amino-treated multi-walled carbon nanotubes and a heat treatment temperature of 550°C can significantly improve the electrochemical performance of the battery, indicating that an appropriate amount of carbon nanotubes can maximize the electrochemical performance of the battery, and controlling the component type of the iron-based selenide by regulating the heat treatment temperature also has a significant effect on optimizing the electrochemical performance.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing an iron-based selenide / carbon nanotube composite material, characterized in that: The method comprises the following steps: S1. Mix stainless steel powder and carbon nanotubes and grind them into a mixed powder, wherein the mass ratio of the stainless steel powder to the carbon nanotubes is 20:1; the stainless steel powder is 420 stainless steel powder; S2, placing the mixed powder and selenium powder described in step S1 in the same device for heat treatment, wherein the mass ratio of the mixed powder to the selenium powder is 1:3, the heat treatment temperature is 550°C, the heat treatment time is 1-7h, and the heating rate is 1-5°C / min. After the heat treatment, the iron-based selenide / carbon nanotube composite material is obtained; The main components of the iron-based selenide / carbon nanotube composite material are Fe3Se4 and Cr2Se3.

2. The method for preparing the iron-based selenide / carbon nanotube composite material according to claim 1, characterized in that: In the step S1, the carbon nanotubes are amino-modified multi-walled carbon nanotubes; In step S2, the heat treatment process is specifically as follows: placing the mixed powder and selenium powder at two ends of a porcelain boat respectively and putting them into a tube furnace for heat treatment under an inert atmosphere.

3. The method for preparing the iron-based selenide / carbon nanotube composite material according to claim 2, characterized in that: The selenium powder is placed at one end of the air inlet, and the mixed powder is placed at one end of the air outlet.

4. An iron-based selenide / carbon nanotube composite material, characterized in that: The iron-based selenide / carbon nanotube composite material is prepared by the method according to any one of claims 1 to 3.

5. A negative electrode sheet for a sodium ion battery, characterized in that: The raw material for preparing the negative electrode sheet of the sodium ion battery comprises the iron-based selenide / carbon nanotube composite material as claimed in claim 4.

6. The negative electrode sheet for a sodium ion battery according to claim 5, characterized in that: The raw materials for preparing the negative electrode sheet of the sodium ion battery also include conductive carbon black and polyvinylidene fluoride, and the mass ratio of the iron-based selenide / carbon nanotube composite material to the conductive carbon black and polyvinylidene fluoride is: iron-based selenide / carbon nanotube composite material: conductive carbon black: polyvinylidene fluoride = (7-8): (1-2):

1.

7. The negative electrode sheet for a sodium ion battery according to claim 6, characterized in that: The negative electrode sheet of the sodium ion battery is prepared by the following method: an iron-based selenide / carbon nanotube composite material, conductive carbon black and polyvinylidene fluoride are ground and mixed, and N-methylpyrrolidone is added dropwise, and stirred evenly, and the obtained slurry is evenly applied to the rough surface of the current collector and vacuum dried to obtain the negative electrode sheet of the sodium ion battery.

8. The negative electrode sheet for a sodium ion battery according to claim 7, characterized in that: The current collector is copper foil.

9. A button battery, characterized in that: The sodium ion battery negative electrode sheet is prepared according to any one of claims 5 to 8, and the negative electrode material of the button battery is metallic sodium, and the electrolyte of the electrolyte is sodium hexafluorophosphate.

10. Use of the iron-based selenide / carbon nanotube composite material according to claim 4 in preparing a negative electrode sheet for a sodium ion battery.

Citation Information

Patent Citations

  • Cobalt selenide / carbon sodium ion battery composite negative electrode material as well as preparation method and application of cobalt selenide / carbon-sodium ion battery composite negative electrode material

    CN105789584A

  • Preparation method and application of iron-based selenide used as sodium-ion battery negative electrode material

    CN113764659A